Self-Presentation in Campaign Discourse: Corpus-Assisted Study (A Case of B. Sanders’s and H. Clinton’s Campaign Speeches) - T. V. Kuraleva; V. N. Kondrashova (Научный диалог)
The paper is devoted to the peculiarities of the implementation of self-presentation strategy in the American campaign discourse. The material included the election speeches of Bernie Sanders and Hillary Clinton, which politicians made during the election campaign from April 2015 to July 2016. The article focuses on the corpus analysis of election speeches. The results of comparative analysis of lexical features of candidates’ pre-election speeches are presented. In addition, the paper proposes a classification of communicative tactics, with the help of which the strategy of self-presentation is implemented (the tactics of self-praise, appeals to former merits, reducing the distance from voters and the tactics of political promises). The analysis allows the authors to make a conclusion about the more aggressive self-presentation of H. Clinton and the important role of personal self-presentation in her speeches. It is shown that B. Sanders focuses on identifying himself with his voters. The analysis of the collocations with components I and we confirms these conclusions. The novelty of the research is seen in the fact that for the analysis of the material from the point of view of pragmatics, the authors use both methods of pragmalinguistic analysis and corpus methods, which makes it possible to present a comprehensive description of the material under study.